AMMONOIDS FROM THE ZHUGANPO MEMBER OF THE FALANG FORMATION AT NIMAIGU AND THEIR RELEVANCE FOR DATING THE XINGYI FOSSIL-LAGERSTÄTTE (LATE LADINIAN, GUIZHOU, CHINA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
We herein document the various ammonoid faunas, of which 8 are newly described taxa, recently collected from the Falang Formation at Nimaigu (Wusha) near Xingyi (Guizhou, South China) and also define their biostratigraphy, correlation and age. The sampled interval includes the Zhuganpo Member, which contains the world famous Xingyi Fossil-Lagerstätte, and the lowermost part of the overlying Wayao Member. Ammonoids are quite abundant, but preservation is usually very poor. New genera Yangites, Haoceras and Sinomeginoceras are described on the basis of four new species. The new subfamily Haoceratinae (family Trachyceratidae) is erected to accommodate Haoceras and Sinomeginoceras. Xenoprotrachyceras, Detoniceras, Ptychites, Trachyceras and Clionitites are also recognized, together with a specimen attributed with doubt to Parasturia.Most of the faunas are endemic and typical representatives of Upper Ladinian ammonoid zones have not been recognized. A new local biostratigraphic scale is proposed, consisting of the Haoceras xingyiense zone, Trachyceras beds and Trachyceras multituberculatum zone, in stratigraphic order.The Trachyceras beds and the Trachyceras multituberculatum zone are attributed to the Lower Carnian, but most of the bio-chronostratigraphic analysis is focused on the Haoceras xingyiense zone, because it directly overlies the vertebrate-bearing interval. Correlation of the new biozone is discussed and its stratigraphic position is referred, at least in part, to the lower Sutherlandi Zone of the North American scale. This correlation pinpoints the age of the Xingyi Fossil-Lagerstätte as middle Late Ladinian, which until now had been a matter of debate for 30+ years.
Keywords: Ammonoidea; Triassic; Ladinian; Taxonomy; Biostratigraphy; Xingyi; Fossil-Lagerstätten; Guizhou; China